Perception of effort in Exercise Science: Definition, measurement and perspectives. Issue 8 (16th November 2016) - Pageaux, Benjamin
Abstract: Perception of effort, also known as perceived exertion or sense of effort, can be described as a cognitive feeling of work associated with voluntary actions. The aim of the present review is to provide an overview of what is perception of effort in Exercise Science. Due to the addition of sensations other than effort in its definition, the neurophysiology of perceived exertion remains poorly understood. As humans have the ability to dissociate effort from other sensations related to physical exercise, the need to use a narrower definition is emphasised. Consequently, a definition and some brief guidelines for its measurement are provided. Finally, an overview of the models present in the literature aiming to explain its neurophysiology, and some perspectives for future research are offered.